Notions of cooperation and articulation of actors in dialogs between the european union and latin america (2008)
This paper seeks to identify the different meanings of international cooperation used in the biregional dialogue between the European Union (EU) and Latin America (LA). With this aim, we critically analyzed the explicit and implicit contents of Ministerial Statements, as well as those by Heads of States from the EU and LA. We first describe the process and the actors involved in the construction of biregional cooperation policy and then analyze both regions’ main features. Next, we explore the different meanings of cooperation and their implications for the relations between the EU and LA.